Die stil van my verlange na God: Oor Johann Wilhelm Herrmann se verstaan van die ervaring van God (Deel II) - Veldsman, D. P. (Verbum et ecclesia, 1997)
Quenching my thirst for God: On Johann Wilhelm Herrmann’s understanding of the experience of God (Part II) This article, which is divided into two parts, focusses on the concept of the "experience of God" as understood by the German systematic theologian Wilhelm Herrmann (1846 - 1922) of Marburg in his "Der Verkehr des Christen mit Gott" (1886). The first part of the article which was published in the previous edition, explained the historical and theological context of Herrmann’s "Der Verkehr..." as well as the theological frontiers over-against which he responded in his understanding of the experience of God, characterized as a "searchfind-experience". This second part elaborates on this "search-find-experience" by humans of God as understood by Herrmann, and indicates the influence it had on Herrmann’s two greatest pupils, namely Karl Barth and Rudolf Bultmann. It is argued that Herrmann’s understanding of the experience of God makes up the kernel of their theological vantage points, and in this respect, is critically evaluated.